Pengembangan Kurikulum Merdeka di SD IT Permata Hati - Ayu Novirianti; Isrowiyah Isrowiyah; Silvi Laila Rista Fauziah; Nabila Fitri Angelika; Didik Efendi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2026)
This paper aims to describe the implementation and development of the Merdeka Curriculum at SD IT Permata Hati Entrop, an Integrated Islamic Elementary School. As an educational institution with a vision of integrating general knowledge with Islamic values, SD IT Permata Hati adapts the national curriculum to create learning that is more flexible, focused on essential content, and character-based. This curriculum is developed to optimize students’ potential holistically, encompassing cognitive, affective, and psychomotor aspects through the strengthening of the Pancasila Student Profile.The main focus of curriculum development at this school consists of three pillars: innovative intracurricular learning, the Project for Strengthening the Pancasila Student Profile (P5), and extracurricular activities that support students’ interests and talents. In its implementation, the school applies active learning methods such as Problem-Based Learning (PBL) and contextual learning linked to daily life and Islamic principles. The evaluation process is conducted through formative and summative assessments that are humanistic and reflective in nature. The outcomes of this development are expected to equip students with 21st-century skills and strong religious character in accordance with the demands of the times.